Hyperostosis frontalis interna and association of disease control with frontal bone thickness in acromegaly - Ihsan Ayhan; Ömercan Topaloğlu; Taner Bayraktaroğlu (BMC Endocrine Disorders)
Abstract Purpose Studies investigating hyperostosis frontalis interna (HFI) in acromegaly are limited. We aimed to investigate HFI and the association of disease control with frontal bone thickness (FBT) in acromegaly. Methods Adult patients with acromegaly were grouped according to the presence of HFI on the baseline MRI: Group 1 absent, Group 2 present. We measured FBT, parietal bone thickness (PBT) and occipital bone thickness (OBT) in the mid-sagittal plane on MRI. The changes between first and last measurements were analyzed. We grouped the patients as controlled vs. uncontrolled acromegaly, and as established disease control for at least 5-year vs. 1-5-years. Results Group 1/Group 2 comprised of 23/29 patients, female/male ratio was 34/18, and mean age 55.41(± 14.21) years. Median follow-up duration was 108 months (6-408). FBTfirst (p = 0.001), FBTlast (p < 0.001), PBTlast (p = 0.025), and OBTlast (p = 0.028) were higher in Group 2 than in Group 1. FBTchange, PBTchange, and OBTchange were positive in Group 2 (p < 0.001, p = 0.008, and p = 0.008; respectively). The ratio of patients with FBT(increased) was higher in Group 2 than in Group 1 (p = 0.001). FBTfirst, FBTlast, PBTfirst, PBTlast, OBTfirst, OBTlast, FBTchange, PBTchange and OBTchange were similar in controlled or uncontrolled acromegaly groups. FBTchange and OBTchange were positive in patients with disease control established for at least 5 years (n = 30) (p = 0.027 and p = 0.002, respectively). Conclusion HFI was common in patients with acromegaly. HFI is associated with a continuous increase in FBT, PBT and OBT. HFI, bone thickness, or increase in bone thickness seems independent of disease activity. Since headaches can be related to an increase in bone thickness, patients should be evaluated and graded during baseline imaging.